2022
DOI: 10.3389/fenvs.2022.908875
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Cumulative Drought Effect on Global Vegetation Photosynthesis Using Numerous GPP Products

Abstract: The increasing trend in drought events under the background of global warming makes it more important to understand the drought effect on vegetation photosynthesis. While diverse global gross primary production (GPP) datasets were adopted to investigate the drought impact on photosynthesis, few studies focused on the discrepancies of drought response among different GPP datasets, especially for the cumulative drought impact. Therefore, a total of twenty-six global GPP datasets based on process, machine learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…This aspect reflects that the future GPP of Chinese grasslands will not consistently increase along with rising CO 2 concentration and warming all the time. With the exception of the temperature-constrained Tibetan Plateau, the carbon sequestration capacity of the other grasslands, which are more sensitive to water (especially drought), will be greatly limited in the future (Wu and Wang 2022). On the other hand, we also be seen that accurately simulating the cold-dry Tibetan Plateau GPP in the future will still be quite difficult.…”
Section: Discussionmentioning
confidence: 96%
“…This aspect reflects that the future GPP of Chinese grasslands will not consistently increase along with rising CO 2 concentration and warming all the time. With the exception of the temperature-constrained Tibetan Plateau, the carbon sequestration capacity of the other grasslands, which are more sensitive to water (especially drought), will be greatly limited in the future (Wu and Wang 2022). On the other hand, we also be seen that accurately simulating the cold-dry Tibetan Plateau GPP in the future will still be quite difficult.…”
Section: Discussionmentioning
confidence: 96%
“…As shown in the figure, the resistance value of the EBF to drought was significantly higher than that of the ENF, indicating that EBF has a stronger drought resistance ability in the subtropical region of China, which is consistent with previous studies ( Huang and Xia, 2019 ; Shao et al., 2022 ). The reason may belong to the higher photosynthesis efficiency of EBF than that of ENF during drought ( Wu and Wang, 2022 ). Previous studies found that EBF could accelerate the loss of old leaves and maintain the growth of young leaves to maintain the light use efficiency, and increase the carbon sequestration capability ( Wu et al., 2016 ; Wei et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the concept of cumulative effects [28], many scholars have further revealed that the intensity of cumulative climatic effects on vegetation growth varies over different growing seasons [29][30][31][32][33][34]. Specifically, a study conducted in Siberia [29] found that climatic factors exhibit an average cumulative effect of 3.6 months on vegetation growth throughout the entire growing season, with more complex ecosystems showing longer cumulative effects.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted in Inner Mongolia [35], it was discovered that temperature and precipitation have a cumulative effect on vegetation growth for up to two months, but the contribution of climatic factors to the current vegetation growth varies depending on the month, with the highest contribution coming from the current month. It has been found that cumulative drought effects impact the photosynthesis process of 52.11% of global vegetation, with an average cumulative duration of 1-4 months [32]. Furthermore, more than three-quarters (78.55%) of grasslands globally are affected by cumulative drought effects, lasting 8-10 months in arid regions of the northern hemisphere (40 • N-55 • N) [31] and 5-10 months in the Qinghai-Tibet Plateau region of China [34].…”
Section: Introductionmentioning
confidence: 99%